Specification for the design of cold-formed stainless steel structural members (ASCE standard, 2002)
'Specification for the Design of Cold-Formed Stainless Steel Structural Members' provides design criteria for the determination of the strength of stainless steel structural members and connections for use in buildings and other statically loaded structures. The members may be cold-formed to shape from annealed and cold-rolled sheet, strip, plate, or flat bar stainless steel material. Design criteria are provided for axially loaded tension or compression members, flexural members subjected to bending and shear, and members subjected to combined axial load and bending. The specification provides the design strength criteria using load and resistance factor design (LRFD) and the allowable stress design (ASD) methods. The reasoning behind and the justification for various provisions of the specification are also presented. The design strength requirements of this Standard are intended for use by structural engineers and those engaged in preparing and administrating local building codes. --